ANALISIS KANDUNGAN LOGAM TIMBAL (Pb) PADA LIPSTIK LOKAL YANG TEREGISTRASI DAN TIDAK TEREGISTRASI BADAN PENGAWAS OBAT DAN MAKANAN (BPOM) SERTA TINGKAT PENGETAHUAN DAN SIKAP KONSUMEN TERHADAP LIPSTIK YANG DIJUAL DI BEBERAPA PASAR DI KOTA MEDAN TAHUN 2015 - pricilia elizabeth; nurmaini *; indra chahaya (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT One of the cosmetics that are often used by women is lipstick. Lipstick can be unsafe if it is polluted by heavy metals such as metallic lead (Pb), which can cause adverse health effects. Lead in lipstick can enter the body through the surface of the skin, digestive and respiratory. Knowledge and attitudes of consumers will shape consumer action in choosing a lipstick product which will be used. The aim of this study was to determine the content of metallic lead (Pb), to determine the level of knowledge and attitudes of consumers towards local lipstick registered and not registered by the Food and Drug Supervisory Agency (BPOM). This research was conducted in several markets in the city of Medan. Present study is a descriptive research in which the consumer population is composed of all consumers who buy lipstick on the location of the research. Samples of consumers from some markets made up of 40 consumers, 55 consumers and 30 consumers. Sample of consumers was taken by accidental sampling method. The data obtained were analyzed descriptively in tables and narrative. The study results showed that 13 samples of local lipstick registered and unregistered by BPOM RI and sold in some markets in the city of Medan after being tested turned out to contain lead in a range of 0,8146-5,5916 mg/kg. The content is still satisfying the requirements according to the regulations of BPOM RI, i.e. £ 20 mg/kg. The level of consumer knowledge about lipstick in multiple markets in the city of Medan consists of moderate knowledge (45,0%) and a good knowledge (55,0%). While the category of consumer attitudes toward lipstick in multiple markets in the city of Medan consists of moderate attitude (21,2%) and a good attitude (78,8%). The conclusion is all the sample of lipsticks products contained lead. BPOM RI is advisable to provide more information about lead-containing lipstick to the public, and consumers are advised to be careful and cautious in choosing a lipstick that will be used. Keywords : Lead (Pb), Registered and Unregistered Local Lipstick, Knowledge and Attitude of Consume